Prognostic Factors Associated With Progression for Advanced-Stage/G1 and G2 Small-Bowel Neuroendocrine Tumors After Multimodal Therapy: Experience From a Tertiary Referral Center. Issue 4 (April 2020) - Khetan, Prerna; Oyewole, Femi; Wolin, Edward; Kim, Michelle Kang; Divino, Celia M.
Abstract : Objectives: Neuroendocrine tumors represent approximately 40% of primary small bowel malignancies. However, factors predictive of progression after multimodal surgical therapy have not been well described. We evaluated the characteristics of small bowel neuroendocrine tumor patients associated with progression after multimodal surgical resection. Methods: A retrospective chart review identified 99 stage III and stage IV small bowel neuroendocrine tumor patients at Mount Sinai diagnosed and treated with surgery between 2005 and 2019. Progression-free survival (PFS) was defined as time from surgery until progression in surveillance radiologic imaging. Kaplan-Meier method was used to calculate PFS. Cox proportional hazard models were used to study the prognostic factors for PFS. Results: Of 99 patients, 48 had tumor progression during the follow-up period. Median PFS was 5.7 years (95% confidence interval [CI], 3.73–8.66) for the entire cohort. Prognostic factors for PFS were age at diagnosis (hazard ratio [HR], 1.04; 95% CI, 1.01–1.07), perineural invasion (HR, 2.19; 95% CI, 1.13–4.23), and elevated preoperative chromogranin level (HR, 2.31; 95% CI, 1.01–5.27). Conclusions: Age at diagnosis, perineural invasion, and elevated preoperative chromogranin level may play a prognostic role in PFS.